2021
DOI: 10.1016/j.ymgmr.2021.100769
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden, management patterns and multidisciplinary clinical approaches for patients with MPS IVA and VI in selected Latin American Countries

Abstract: Background There is a paucity of real-world epidemiological data on patients with mucopolysaccharidoses (MPS) in Latin America. This real-world study assessed the disease burden, management patterns and multidisciplinary clinical approaches for MPS-IVA and MPS-VI patients in Latin America (Colombia, Ecuador, Mexico, Peru). Methods Data were collected from physicians/specialists experienced in treating MPS patients between April–June 2020, via an online patient-diary sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…A total of 64.1% of MPS patients who go to school or work miss an entire day every week due to ERT. High absenteeism from school or work has also been reported by Solano et al 15 in MPS-IVA and VI patients from Latin America, but mostly due to disease burden and progression, and its relation to ERT was largely unexplored. In already disadvantaged patients with sensory, motor, and/or learning disabilities, 20% absence from school or work solely due to ERT should be avoided.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A total of 64.1% of MPS patients who go to school or work miss an entire day every week due to ERT. High absenteeism from school or work has also been reported by Solano et al 15 in MPS-IVA and VI patients from Latin America, but mostly due to disease burden and progression, and its relation to ERT was largely unexplored. In already disadvantaged patients with sensory, motor, and/or learning disabilities, 20% absence from school or work solely due to ERT should be avoided.…”
Section: Discussionmentioning
confidence: 80%
“…Patients living in Central Anatolia (in provinces other than Ankara) and Eastern Anatolia, especially in small settlements, have a disadvantage in obtaining drug doses and continuing ERT without interruption. The study by Solano et al 15 has shown that ERT interruption due to temporary unavailability of the drug is similarly common in Latin America, but this did not differ significantly among urban and rural areas. It is possible that the apparent influence of geographical factors is confounded by economic, social, and cultural factors not addressed in our study and is probably only a part of well-known regional health disparities, 22 requiring broader socioeconomic and public health interventions for improvement.…”
Section: Discussionmentioning
confidence: 93%